Pengeluaran Pemerintah, Investasi dan Pertumbuhan Ekonomi Provinsi Bengkulu Tahun 2016-2021 - Mimi Filma Herita; Yuhendri L V (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2023)
Economic growth is a macroeconomic problem that occurs in Bengkulu Province. This study aims to analyze the effect of government spending and investment on economic growth in Bengkulu province. The data analysis technique uses panel data regression using secondary data from 9 regencies and 1 city in Bengkulu province in the 2016-2021 range which was sourced from the Central Bureau of Statistics of Bengkulu Province. The results of the study show that government spending and investment simultaneously have a positive and significant effect on economic growth. Government spending has a positive and significant effect on economic growth, Domestic Investment Investment (PMDN) has a positive and significant effect on economic growth, while Foreign Direct Investment (PMA) has no effect on economic growth in Bengkulu province. The results of this study can be used as a guideline for the formulation of Bengkulu provincial government in increasing economic growth by increasing government spending and investment.